Study on Packaging Technology of GAGG:Ce Scintillation Detector - WAN Qianyin1, 2, WANG Qiang1, 2, XIE Yuqing1, 2, XIAO Xiong1, 2, ZHANG Zetao1, 2, DING Yuchong1, 2, REN Kejing1, 2, XU Yang1, 2 (Yuanzineng kexue jishu)
GAGG:Ce scintillation crystal has a wide application prospect in the field of energy spectrum detection, due to its high density, high light yield, radiation resistance and non-deliquination characteristics. The performance of the GAGG:Ce scintillator detector is limited, especially its energy resolution (a parameter mainly affected by the efficiency of the scintillation photon collection), in the packaging methods of reference deliquing crystals. In order to improve the scintillation photon collection efficiency of the new scintillation crystal GAGG:Ce in the radiation detector package, the package technology of the GAGG:Ce scintillation crystal with ϕ25.4 mm×25.4 mm in size was studied using Geant4 simulation and comparison experiments. In scintillator package, crystal surface processing, reflector material and thickness, optical coupler and photoelectric conversion device are important factors that affect the photon collection efficiency of detector. Firstly, the photon collection efficiency with specular reflector and diffuse reflector was analyzed under the conditions of crystal surface is specular and fleeced respectively, based on Geant4 LUT photon transport model. It is determined that the diffuse reflection on the crystal surface is the most conducive to the collection of scintillation photons. Secondly, the light output of the crystal under the four reflector layers of ESR film, Teflon tape, BaSO4 coating and TiO2 coating was compared in the experiment, and the TiO2 coating has the best performance. And the light output of the reflector with a thickness of 0.5-2 mm was compared when the reflector on the crystal surface was a TiO2 coating. Thirdly, in view of the effect of the refractive index of the optical glue on the photon collection efficiency of the coupling crystal and PMT, the optical output of the detector under the coupling of 6 different refractive index optical glue (1.43-1.70) was compared. Finally, the emission spectrum of GAGG:Ce scintillator was analyzed, and its peak wavelength is 550 nm. The energy resolutions of three kinds of PMT (CR125, CR173, R6231-100) and SiPM (J60035) were studied when they were used as scintillator photoelectric conversion devices respectively. To package a GAGG:Ce radiation detector with superior scintillation photon collection efficiency, an optical adhesive with a refractive index of 1.70 is coupled with HAMAMMATSU R6231-100 photomultiplier tube. The resulting energy resolution stands at 4.68% (@662 keV).